1988
DOI: 10.1084/jem.167.5.1731
|View full text |Cite
|
Sign up to set email alerts
|

Age-related galactosylation of the N-linked oligosaccharides of human serum IgG.

Abstract: Immunological competence is known to vary with age, and such age-related variations are often parabolic in nature . For example, both the level and avidity of the antibody response increase during postnatal development, reach a maximum in adulthood, and then decline during senescence (1). Cellular changes in the T lymphocyte compartment (both helper and suppressor T cell levels) appear to account for most variations in immunological competence (1, 2). Relatively few studies have attempted to correlate these fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
168
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(190 citation statements)
references
References 12 publications
(21 reference statements)
21
168
1
Order By: Relevance
“…Interestingly, elevated levels of agalactosyl glycoforms were found in female RA patients, while decreased levels were correlated with disease remission during gestation followed by postpartum recurrence [50]. The glycoform distribution of serum IgG was shown to change with age [51,52]. It has been suggested that low galactosylation of IgG may have a critical role in the pathology of autoimmune disorders such as RA and SLE [53][54][55], but can also occur through aging [56].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated levels of agalactosyl glycoforms were found in female RA patients, while decreased levels were correlated with disease remission during gestation followed by postpartum recurrence [50]. The glycoform distribution of serum IgG was shown to change with age [51,52]. It has been suggested that low galactosylation of IgG may have a critical role in the pathology of autoimmune disorders such as RA and SLE [53][54][55], but can also occur through aging [56].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the relative incidence of digalactosylated structures (G2) changes inversely to G0 whereas monogalactosylated structures are constant in both sexes (23). A high G0/ G1 or G0/G2 ratio indicates a higher level of agalactosylated structures relative to mono-or diagalactosylated N-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…We determined peak % areas of agalactosylated (G0), mono-(G1) and digalactosylated (G2) structures to provide a quantitative measurement of galactose incorporation into released undigested IgG N-glycans. We focused on the G0/ G2 ratio because digalactosylated (G2) structures were found to vary more than (G1) structures which remain more constant in healthy individuals (6,23). The technical replicate coefficients of variations for IgG N-glycans was below 10%.…”
Section: Soluble Leptin Receptor (Sob-r)mentioning
confidence: 99%
“…No difference was seen in the level of expression of the protein kinase gene in pooled E+ or pooled E-lymphocytes of normal individuals (Figure 6). Furthermore, the level of expression of this gene did not appear to be substantially different in pooled lymphocytes from RA patients, whether the RNA was obtained from patients with a glycosylation defect (i.e., percentage of oligosaccharide chains lacking galactose is >2 SD from the mean of normal control values [30]) or from patients with normally glycosylated IgG (i.e., percentage of oligosaccharide chains lacking galactose is <2 SD from the mean of normal control values). Slight differences in intensity between the samples hybridized with the GTA protein kinase gene probe were shown, by rehybridization with a pactin probe, to be largely due to variations in the amount of RNA bound to the nylon membranes.…”
Section: Resultsmentioning
confidence: 95%